1996
DOI: 10.1111/j.1748-5827.1996.tb02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of external skeletal fixators in the repair of femoral fractures in cats

Abstract: This paper reports the results of fixation of 35 femoral fractures in cats using an external skeletal fixator alone or in combination with supplementary devices. All the fractures healed. The average time to fixator removal was eight weeks and two days. The external skeletal fixator offers a method of repairing many types of femoral fractures in cats allowing sound orthopaedic principles to be maintained and producing a successful outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 17 publications
2
26
0
Order By: Relevance
“…They concluded that there remains a place for their use in the femur when correctly applied and plate fixation may not be an optimal choice for all fractures given that application can be expensive. 27 This conclusion is supported by a population of dogs and cats undergoing femoral fracture stabilisation with modified acrylic ESFs in which 100% of the dogs and none of the cats developed an FAC. 28 Implant failure had an overall incidence of 9%, representing 41% (n=12) of all complications.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They concluded that there remains a place for their use in the femur when correctly applied and plate fixation may not be an optimal choice for all fractures given that application can be expensive. 27 This conclusion is supported by a population of dogs and cats undergoing femoral fracture stabilisation with modified acrylic ESFs in which 100% of the dogs and none of the cats developed an FAC. 28 Implant failure had an overall incidence of 9%, representing 41% (n=12) of all complications.…”
Section: Discussionmentioning
confidence: 89%
“…IM pins are commonly used at these sites to help fracture alignment and to improve resistance to bending. 27,44 Their location of use will also be influence by the regional anatomy, as some bones lend themselves to adjunctive IM pin fixation, such as the femur, humerus and tibia, however fracture configuration such as comminution will also be a consideration. It is important to note therefore that their risk association may be a surrogate marker for their usage in higher risk zones, or higher risk fracture configurations.…”
Section: Discussionmentioning
confidence: 99%
“…This complication occurred in all of the dogs in this case series but did not result in noticeable lameness. Interestingly, no mention of such complication was reported in previous studies in which "tie-in" configuration was used for the management of femoral fractures in dogs (1) and cats (10). However, since the wound healed and draining stopped after removing the IM pin, this was considered as a minor complication.…”
Section: Discussionmentioning
confidence: 94%
“…Conservative treatment often results in normal use of the affected limb and normal growth of the animal [9]. Prognosis with conservative treatment is improved when the fracture is minimally displaced, the animal is young, and the radial nerve is intact [16].…”
mentioning
confidence: 99%